Text Mining to Alleviate the Cold-Start Problem of Adaptive Comparative Judgments - De Vrindt, Michiel; Van den Noortgate, Wim; Debeer, Dries (Frontiers in Education, 2022)
Comparative judgments permit the assessment of open-ended student works by constructing a latent quality scale through repeated pairwise comparisons (which works \lq win\rq \ or \lq lose\rq). Adaptive comparative judgments speed up the judgment process by maximizing the Fisher information of the next comparison. However, at the start of a judgment process, such an adaptive algorithm will not perform well because in order to reliably approximate the Fisher Information of possible pairs well, multiple comparisons are needed. In addition, adaptive comparative judgments have been shown to inflate the scale separation coefficient, which is a reliability estimator for the quality estimates. Current methods to solve the inflation issue increase the number of required comparisons. The goal of this study is to alleviate the cold-start problem of adaptive comparative judgments for essays or other textual assignments, but also to minimize the bias of the scale separation coefficient. By using text-mining techniques, which can be performed before the first judgment, essays can be adaptively compared from the start. More specifically, we propose a selection rule that is based both on a high (1) cosine similarity of the vector representations and (2) Fisher Information of essay pairs. At the start of the judgment process, the cosine similarity has the highest weight in the selection rule. With more judgments, this weight decreases progressively, whereas the weight of the Fisher Information increases. Using simulated data, the proposed strategy is compared with traditional approaches. The results indicate that the proposed selection rule can mitigate both the cold-start. That is, less judgments are needed to obtain accurate and reliable quality estimates. In addition, the selection rule was found to reduce the inflation of the scale separation reliability.